Targeting 17β-estradiol biosynthesis in neural stem cells improves stroke outcome - Patkar, Shalmali; Uwanogho, Dafe; Modo, Michel; Tate, Rothwelle J.; Plevin, Robin; Carswell, Hilary V. O. (Frontiers in Cellular Neuroscience, 2022)
Dax-1 (dosage-sensitive sex reversal adrenal hypoplasia congenital region on X-chromosome gene 1) blocks 17β-estradiol biosynthesis and its knockdown would be expected to increase 17β-estradiol production. We hypothesized that knockdown of Dax-1 in a conditionally immortalized neural stem cell (NSC) line, MHP36, is a useful approach to increase 17β-estradiol production. Short hairpin (sh) RNA targeted to Dax-1 in NSCs, namely MHP36-Dax1KD cells, resulted in the degradation of Dax-1 RNA and attenuation of Dax-1 protein expression. In vitro, MHP36-Dax1KD cells exhibited overexpression of aromatase, and increased 17β-estradiol secretion compared to MHP36 cells. As 17β-estradiol has been shown to promote efficacy of cell therapy, we interrogated the application of 17β-estradiol-enriched NSCs in a relevant in vivo disease model. We hypothesized that MHP36-Dax1KD cells will enhance functional recovery after transplantation in a stroke model. C57BL/6 male adult mice underwent ischemia/reperfusion by left middle cerebral artery occlusion for 45 minutes using an intraluminal thread. Two days later male mice randomly received vehicle, MHP36 cells, MHP36-Dax1KD cells, MHP36 cells suspended in 17β-estradiol (100nM) or 17β-estradiol alone (100nM) with serial behavioural testing over 28 days followed by post-mortem histology and blinded analysis. Recovery of sensorimotor function was accelerated and enhanced, and lesion volume was reduced by MHP36-Dax1KD transplants. Regarding mechanisms, immunofluorescence indicated increased synaptic plasticity and neuronal differentiation after MHP36-Dax1KD transplants. In conclusion, knockdown of Dax-1 is a useful target to increase 17β-estradiol biosynthesis in NSCs and improves functional recovery after stroke in vivo, possibly mediated through neuroprotection and improved synaptic plasticity. Therefore, targeting 17β-estradiol biosynthesis in stem cells may be a promising therapeutic strategy for enhancing efficacy of stem cell-based therapies for stroke.